Efficacy of Platelet Rich Plasma in Erectile Dysfunction: A Clinical Trial - Khan, Asma Tasnim; Hashem, Md Abul; Hassan, Muhammed Kamrul; Jakia, Mahfuja; Sarkar, Nayanmani; Sakib, Mohammad Irfan Ullah; Jahan, Sharmin (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Platelet-rich plasma (PRP) is a treatment that uses a patient's own blood, processed to concentrate platelets and growth factors, to treat erectile dysfunction (ED). Erectile dysfunction (ED) is a common condition that affects men of all ages and can have a significant impact on quality of life. Platelet rich plasma (PRP) is a newer treatment option that involves injecting a concentrated solution of platelets into the affected area to promote healing and tissue regeneration. Objective: The purpose of the present study was to evaluate the efficacy of platelet-rich plasma (PRP) in treating erectile dysfunction (ED). Methodology: A prospective study was conducted to evaluate the efficacy of platelet-rich plasma (PRP) in treating erectile dysfunction (ED) with a sample of 50 patients in Dhaka, Bangladesh during the period of January 2022 to June 2022. The patients received PRP treatment and the improvement in erectile function was measured through standardized questionnaires and scales. Data were collected predesigned data collection sheet. Results: The average age of the study subjects is 53.70 years. The mean scores of the IIEF-EF domain showed a statistically significant improvement from 18.50 ± 3.60 before the procedure to 20.71 ± 3.71 after 6th months (p = 0.002). Sexual satisfaction also showed a statistically significant improvement, with a mean score increasing from 6.00 ± 0.57 before the procedure to 8.00 ± 0.85 after 6th months (p = 0.016). However, there were no statistically significant changes in the mean scores for orgasmic function and sexual desire (p = 0.113 and p = 0.389, respectively). The mean score for general satisfaction showed a small but statistically significant increase from 5.00 ± 0.29 before the procedure to 5.38 ± 0.24 after the 1st month (p = 0.027). Conclusion: In conclusion platelet-rich plasma (PRP) application provides short-term improvement in erectile function. Journal of National Institute of Neurosciences Bangladesh, January 2023;9(1):71-75